2020
DOI: 10.3390/ani10030415
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprint of Mediterranean Pasture-Based Native Beef: Effects of Agronomic Practices and Pasture Management under Different Climate Change Scenarios

Abstract: A better understanding of soil organic carbon (SOC) dynamics is needed when assessing the carbon footprint (CFP) of livestock products and the effectiveness of possible agriculture mitigation strategies. This study aimed (i) to perform a cradle-to-gate CFP of pasture-based beef cattle in a Mediterranean agropastoral system (ii) and to assess the effects on the CFP of alternative tillage, fertilizing, and grazing practices under current (NCC) and future climate change (CC) scenarios. Minimum (Mt) and no-tillage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Cities are the areas where human activities have the greatest impact on the surface. Accelerated urbanization and urban expansion have had a profound impact on the global carbon cycle and climate change [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cities are the areas where human activities have the greatest impact on the surface. Accelerated urbanization and urban expansion have had a profound impact on the global carbon cycle and climate change [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…An open-source tool 2 developed by the WRI has been used for the quantitative uncertainty assessment of the annual GHG emission arising from the Reserve. Differently, the uncertainty range provided for the annual C-sinks rates coming from the agricultural soil (Grossi et al, 2020) and the aboveground forest growth (Scrinzi et al, 2019) were those reported by the authors of the estimations.…”
Section: Uncertainty Assessmentmentioning
confidence: 87%
“…A Tier 3 approach involving the use of a process-based model named the Denitrification-Decomposition (DNDC) model (Li et al, 2000) was used for the assessment of GHG emissions (i.e., CH 4 , direct and indirect N 2 O) coming from the manure deposited on pasture by cattle (Grossi et al, 2020). A Tier 1 (Velthof, 2014;IPCC, 2019) approach was used for the estimations of the GHG from both horses and wild fauna' manure (Supplementary Table S10 [3-4]).…”
Section: Direct Greenhouse Gas Emissions and Removalsmentioning
confidence: 99%
See 2 more Smart Citations